(untitled) (Scientific journal of the Fergana State University, 2024)
A comparative study of linguistic units with an ornithonym component in different systematic languages, a study of the lexical-semantic and systematic structure of the word as a linguistic unit and an ornithonym, linguistic units representing bird names from a national-cultural point of view, as well as they are analyzed on semantic, syntactic and structural research of bird names as components of phraseological units in Uzbek and world linguistics.